Local analysis of the feasible primal-dual interior-point method - Silva, R. (2008)
Abstract In this paper we analyze the rate of local convergence of the Newton primal-dual interior-point method when the iterates are kept strictly feasible with respect to the inequality constraints. It is shown under the classical conditions that the rate is q-quadratic when the functions associated to the binding inequality constraints are concave. In general, the q-quadratic rate is achieved provided the step in the primal variables does not become asymptotically orthogonal to any of the gradients of the binding inequality constraints. Some preliminary numerical experience showed that the feasible method can be implemented in a relatively efficient way, requiring a reduced number of function and derivative evaluations. Moreover, the feasible method is competitive with the classical infeasible primal-dual interior-point method in terms of number of iterations and robustness.